2015
DOI: 10.1016/j.sbspro.2015.01.493
|View full text |Cite
|
Sign up to set email alerts
|

Technology Based Counseling: Perspectives of Turkish Counselors

Abstract: The purpose of this study is to analyze the Turkish counselors' perspectives about using Internet for counseling purposes in their professional life. The questionnaire prepared by the researchers based on literature review and experts' opinion. It was sent to counselors via e-mail, 542 counselors returned the questionnaire. Findings were analyzed by using descriptive statistics.Counselors' perspectives about online counseling were also examined by content analysis. Results indicated that counselors have positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 20 publications
2
31
0
10
Order By: Relevance
“…Zeren (2015) concluded that online clients' satisfaction with the process is as high as face-to-face clients. Again some research studies (Bastemur & Bastemur, 2015;Tanrıkulu, 2009) revealed positive attitudes towards online counseling. In this study, prejudices about online counseling, in other words negative attitudes, may have intervened.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeren (2015) concluded that online clients' satisfaction with the process is as high as face-to-face clients. Again some research studies (Bastemur & Bastemur, 2015;Tanrıkulu, 2009) revealed positive attitudes towards online counseling. In this study, prejudices about online counseling, in other words negative attitudes, may have intervened.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Zeren (2015) ise süreçten yararlanmaya ilişkin olarak çevrimiçi danışanların memnuniyetinin, yüz yüze danışanlar kadar yüksek olduğu sonucuna ulaşmıştır. Yine bazı araştırmalar (Bastemur & Bastemur, 2015;Tanrıkulu, 2009) çevrimiçi danışmaya ilişkin olumlu tutumlar ortaya koymuştur. Ancak, bu çalışmada çevrimiçi psikolojik danışmaya ilişkin ön yargılar, başka bir ifadeyle olumsuz tutumlar, devreye girmiş olabilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…The study conducted by Marin & Bocoș (2018), revealed that according to the school principals' and the teachers' opinions, organizing meetings and lectures with the parents is one of the most effective strategies for consolidating the school familypartnership. Bastemur & Bastemur (2015) considered that online counseling has multiple advantages, but significant challenges can also be encountered. It is unanimously accepted that the family climate and the degree of family involvement in children's education has a decisive influence over the pupil's development (Bodovski & Youn, 2010).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Based on the literature, it is well known that one of the reasons related to the use of technology by counselors is the counseling session can be done directly through their gadgets in anywhere and anytime. Furthermore, Bastemur & Bastemur [8] revealed that counselors feel positive sides of using online counseling although most of the counselors think that they do not have enough knowledge about online counseling.…”
Section: Bk Online Servicesmentioning
confidence: 99%
“…Online counseling is a therapy which is not categorized as a strict therapy but it may also contain consultation for the improvement of mental and behavioral health through phone, e-mail, synchronous chat, and video conferencing [8]. According to [9], the familiarity with technology and the calm in facing technical problems are the keys to provide a better experience in online counseling.…”
Section: Introductionmentioning
confidence: 99%